Misconduct in scientific publication: a risk to life - Eleutério Jr, José (Brazilian Journal of Sexually Transmitted Diseases, 2020)
During a SARS-CoV-2 infection pandemic, there was also a “pandemic” of scientific articles written and published at a dreadful speed. Thus, due to their own haste, journals have made available to the medical and scientific community several studies with evident biases, which culminated in the publication “Hydroxychloroquine or Chloroquine With or Without a Macrolide for Treatment of COVID-19: A Multinational Registry Analysis” in the renowned journal The Lancet(1), with considerable controversy and need for retraction. [...]